Analysis of surgical and therapeutic interventions in patients with craniopharyngioma undergoing open transcranial resections versus endoscopic endonasal resections: A systematic review - Daniel Encarnacion-Santos; Ismail Bozkurt; Gennady Chmutin; Egor Chmutin; Murat Pashev; Bipin Chaurasia; Nazmin Ahmed; Emmanuel Batista-Geraldino; Baraniko Eromanga (Annals of Oncology Research and Therapy, 2025)
Craniopharyngiomas (CPMs) are uncommon embryonic anomalies located in the sellar and parasellar regions, characterized by their exceedingly low histological grade (WHO I). The incidence of 1-3 new cases per million each year globally. The aim of this systematic review is to conduct a comparative analysis of EEN and TC therapies, irrespective of the total number of patients who received alternative interventions. Two primary subtypes of CPMs have been recognized: papillary, predominantly observed in adults, and adamantinomatous, primarily found in children and resembling neoplasms that generate enamel-like structures in the oropharynx. Adults with the adamantinomatous variant are associated with mutations in the β-catenin gene, a key mediator of the Wnt CTNNB1 pathway, while adults with the BRAF V600E mutation are frequently associated with the papillary subtype. Materials and Methods: Following that, the scientific literature is examined using the Preferred Reporting Items for Systematic Reviews (PRISMA) Direct and PubMed/MEDLINE through January-August 2024. The IBM SPSS Statistics for Windows, Version 26.0 (released 2020; IBM Corp., Armonk, New York, United States) and EXCEL criteria were used for the statistical study. Results: This comprehensive analysis includes 3076 patients with craniopharyngiomas. Among these, 1339 patients had endoscopic endonasal resections, whereas 591 patients underwent open transcranial resections. For this form of pathology, endoscopic resection was the more favorable alternative. Conclusion: We discovered that craniopharyngiomas Because total eradication is not achieved, recurrences are common, therefore elimination by new intervention, plus adjuvant radiation or chemotherapy, plus surgery.